Analisis Implementasi Kebijakan Penyelenggaraan Kearsipan di Direktorat Jenderal Otonomi Daerah Kementerian Dalam Negeri - Nirwana, Tian (UI Scholars Hub, 2022)
This study aims to analyze the implementation of archival policies in the Directorate General of Regional Autonomy, Ministry of Home Affairs (Ditjen Otonomi Daerah Kemendagri). This research was conducted using a postpositivist approach and qualitative data collection techniques in the form of observation, interviews and documentation studies. The results of the study indicate that almost all the variables of policy implementation support the archival implementation at the Directorate General of Regional Autonomy. However, there are still some indicators that need to be improved, namely the limited number of archiving Human Resources (SDM), the mindset of the State Civil Apparatus (ASN) towards archival management and the absence of Archival Standard Operating Procedures (SOP).